A basic study on novel islanding detection method for photovoltaic inverters by positive feedback of harmonic voltage. Issue 1 (1st January 2016) - Yoshida, Yoshiaki; Suzuki, Hirokazu
Abstract: We have proposed an islanding detection method using the harmonic current as an active signal. In particular, in order to inject the active signal efficiently, we have proposed a method to synchronize the harmonic voltage caused by the active signal of DG with the harmonic voltage caused by the harmonic current of the load. To verify the validity of the proposed methods, we performed the simulation by PSCAD/EMTDC and the calculation by circuit theory. We clarified that the synchronous injection can be greatly reduced the islanding detection time.